2019
DOI: 10.1177/0193945919868143
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Restriction Effects on BP: Systematic Review & Meta-analysis of RCTs

Abstract: This systematic review and meta-analysis aimed to examine the effect of sleep restriction on blood pressure (BP) among healthy adults. Randomized controlled trials (RCTs) using partial sleep deprivation were included. The pooled effect size was calculated by the inverse variance method, and forest plot was used. Six studies were included (n = 10–43). Only one study obtained continuous BP readings. Overall, sleep restriction did not result in significant changes in systolic blood pressure (SBP) or diastolic blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Autonomic function is associated, at least in part, with HR and BP (43), and may explain the association between insufficient sleep and cardiac activity. Finally, future studies should be conducted with comparison groups and fewer study procedures unrelated to cardiac activity measurement (e.g., blood draws) to better ascertain the effects of sleep restriction on HR and BP (21).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic function is associated, at least in part, with HR and BP (43), and may explain the association between insufficient sleep and cardiac activity. Finally, future studies should be conducted with comparison groups and fewer study procedures unrelated to cardiac activity measurement (e.g., blood draws) to better ascertain the effects of sleep restriction on HR and BP (21).…”
Section: Limitationsmentioning
confidence: 99%
“…A similar study found that systolic BP (SBP), but not HR, remained elevated during recovery after more than a week of sleep restricted to 4 hours/ night (20). Conversely, other studies have not found consistent changes in HR or BP after sleep restriction (15,16,21,22).…”
Section: Introductionmentioning
confidence: 96%
“…[9][10][11] However, most of the studies investigating BP changes during prolonged exposure to partial sleep deprivation (namely sleep restriction)-an experimental model that mimics the low-grade cumulative sleep loss experienced in real life-have reported more ambiguous findings, [11][12][13][14][15][16][17] yielding, in aggregate, no evidence that sleep restriction raises BP. 18 It is relevant that in nearly all studies, BP assessment was limited to only resting BP readings, and samples were often restricted to men. 12,14,15 With this study, we sought to evaluate the effects of experimentally induced prolonged sleep restriction on 24-hour ambulatory BP in healthy young adults.…”
Section: Covassin Et Almentioning
confidence: 99%
“…There is considerable evidence that associations exist between sleep and health status [1][2][3][4][5]. Most notably, strong and consistent associations have been observed between short sleep durations (generally defined as 6 h or less) and various diseases and adverse health outcomes, such as type 2 diabetes, cardiovascular disease and obesity, or their correlates [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%